SAP S/4HANA Cloud Public to Private Edition Upgrade: Strategy to Implementation - Eko Haryadi; Eka Chandra; Diah Wijayanti; Juniarti Eka Sapitri (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
Data mapping from legacy systems to new systems is also required because an effective SAP S/4HANA data model removes redundancy and integrates data more successfully. This is because legacy systems frequently store data in a format that is incompatible with SAP S/4HANA initiatives. Data quality is another problem. Over time, a lot of useless, out-of-date, or erroneous data can build up in legacy systems. This article aims to give a summary of the SAP S/4HANA public to private upgrade process and then assess how businesses may use real-time analytics, increase operational efficiency, and guarantee business continuity with a more adaptable and secure cloud platform. The SAP Activate Methodology, an official framework from SAP that includes project phases, tasks, and deliverables to guarantee that upgrading is organized, effective, and in accordance with business goals. This research's main contribution is to enrich the body of knowledge on enterprise systems migration and digital transformation by documenting best practices and lessons learned from actual upgrading initiatives. This study assesses how switching to SAP S/4HANA enhances productivity, analytics, and compliance and provides a methodology for organizing, carrying out, and tracking SAP upgrades.